Potential role for anti‐angiogenic therapy in abdominal aortic aneurysms. (14th May 2013) - Vijaynagar, Badri; Bown, Matt J.; Sayers, Robert D.; Choke, Edward
Abstract Objective Abdominal aortic aneurysm (AAA) is a condition that mainly affects elderly men. At present, there is no effective medical therapy that can retard aneurysm growth or prevent aneurysm rupture. There is evidence that angiogenesis within the wall of an aortic aneurysm may play key roles in aneurysm progression as well as rupture. The use of anti‐angiogenic therapy as potential medical therapy in AAA is a promising strategy but has never been studied in detail. Design This paper discusses the basic mechanisms of angiogenesis, the role played by angiogenesis in aortic aneurysms and the potential therapeutic role of anti‐angiogenic drugs against aneurysm expansion or rupture. Results Angiogenesis is a multi‐step process which is fundamental for growth and differentiation of various tissues within a multi‐cellular organism. Hypoxia and inflammation are key stimuli for activation of neoangiogenesis. Investigations in both human tissues and animal models of AAA have shown that angiogenesis is a pathological hallmark of AAA and appears to play a role in the development and progression of the condition. Pre‐clinical studies have shown that anti‐angiogenic drugs can potentially be effective in reducing the intensity of aneurysm formation, suggesting that such drugs may potentially be useful as novel drug therapy for AAA in humans. Conclusion Current evidence suggests that angiogenesis contributes to the destructive processes within aneurysmal aortic wall. As novel drug therapy for aortic aneurysms (for use in humans) is still eluding researchers, anti‐angiogenic pathway appears to be an attractive approach.